2021
DOI: 10.1038/s41550-021-01508-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Breakthrough Listen signal of interest blc1 with a technosignature verification framework

Abstract: The aim of the search for extraterrestrial intelligence (SETI) is to find technologically capable life beyond Earth through their technosignatures. On 2019 April 29, the Breakthrough Listen SETI project observed Proxima Centauri with the Parkes ‘Murriyang’ radio telescope. These data contained a narrowband signal with characteristics broadly consistent with a technosignature near 982 MHz (‘blc1’). Here we present a procedure for the analysis of potential technosignatures, in the context of the ubiquity of huma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Smith et al (2021) described the BL search for radio technosignatures from the direction of Proxima Centauri using the Parkes Murriyang radio telescope and the detection of blc1. Its companion paper, Sheikh et al (2021a), presented the analysis of the technosignature candidate, which determined that the signal was not extraterrestrial, and instead produced by Earth-based electronics. Follow-up observations of Proxima Centauri by Sheikh et al (2021b) found no repeats of blc1 or any other signals of interest near the same wavelength.…”
Section: Results From Searches (15 Papers)mentioning
confidence: 99%
“…Smith et al (2021) described the BL search for radio technosignatures from the direction of Proxima Centauri using the Parkes Murriyang radio telescope and the detection of blc1. Its companion paper, Sheikh et al (2021a), presented the analysis of the technosignature candidate, which determined that the signal was not extraterrestrial, and instead produced by Earth-based electronics. Follow-up observations of Proxima Centauri by Sheikh et al (2021b) found no repeats of blc1 or any other signals of interest near the same wavelength.…”
Section: Results From Searches (15 Papers)mentioning
confidence: 99%
“…More broadly, our likelihood emulation approach provides an example of dealing with sparse, irregular observations to conduct inference of SETI signals of interest. Indeed this approach could be readily applied to other technosignature data sets, such as the Breakthrough Listen radio search (Price et al 2020;Sheikh et al 2021) or even non-radio searches such as in the optical (e.g. see Maire et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Previous targeted SETI studies have accumulated rich experience in identifying candidate signals and established a systematic methodology. Aiming to compare our approach to the former ones and complement the signal identification methodology, we performed a comprehensive examination on NBS 210629 following the technosignature verification framework summarized by Sheikh et al (2021).…”
Section: Complements To Technosignature Verification Methodologymentioning
confidence: 99%
“…6. Corresponding to the steps 6-9 in Sheikh et al (2021), we search our data for RFI signals with similar characteristics to NBS 210629, which may have the same origin with the event. Because a signal may be transmitted at several different frequencies simultaneously, and the frequency of a signal may always be constant, our search is carried out in two directions: (1) RFI with the same frequency-normalized drift rate ν/ν in the same observation;…”
Section: Complements To Technosignature Verification Methodologymentioning
confidence: 99%